Genetic deficiency of protein inhibitor of activated STAT3 suppresses experimental abdominal aortic aneurysms - Fu, Weilai; Liu, Haole; Wei, Panpan; Xia, Congcong; Yu, Qingqing; Tian, Kangli; Li, Yankui; Liu, Enqi; Xu, Baohui; Miyata, Masaaki; Wang, Rong; Zhao, Sihai (Frontiers in Cardiovascular Medicine, 2023)
Aim: Signal transducer and activator of transcription (STAT) signaling is critical for the pathogenesis of abdominal aortic aneurysms (AAAs). Though protein inhibitor of activated STAT3 (PIAS3) negatively modulates STAT3 activity, but its role in AAA disease remains undefined. Method: AAAs were induced in PIAS3 deficient (PIAS3-/-) and wild type (PIAS3+/+) male mice via transient intra-aortic elastase infusion. AAAs were assessed by in situ measurements of infrarenal aortic external diameters prior to (day 0) and 14 days after elastase infusion. Characteristic aneurysmal pathologies were evaluated by histopathology. Results: Fourteen days following elastase infusion, aneurysmal aortic diameter was reduced by an approximately 50% in PIAS3-/- as compared to PIAS3+/+ mice. On histological analyses, PIAS3-/- mice showed less medial elastin degradation (media score: 2.5) and smooth muscle cell loss (media score: 3.0) than those in PIAS3+/+ mice (media score: 4 for both elastin and SMC destruction). Aortic wall leukocyte accumulation including macrophages, CD4+ T cells, CD8+ T cells and B cells as well as mural neovessel formation were significantly reduced in PIAS3-/- as compared to PIAS3+/+ mice. Additionally, PIAS3 deficiency also downregulated the expression levels of matrix metalloproteinases 2 and 9 by 61% and 70%, respectively, in aneurysmal lesion. Conclusion: PIAS3 deficiency ameliorated experimental AAAs in conjunction with reduced medial elastin degradation and smooth muscle cell depletion, mural leukocyte accumulation and angiogenesis.